2022
DOI: 10.1128/spectrum.02158-21
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Multidrug Resistant Klebsiella pneumoniae Pathogenic Clones of Human Relevance in an Equine Pneumonia Case

Abstract: Multidrug resistant Klebsiella pneumoniae are agents of life-threatening infections in animals and humans, with several multidrug resistant clones causing outbreaks of disease worldwide. It is generally accepted that only one clone will be dominant in an infection episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…For example, this study did not use a pre-enrichment step for ESBL- and AmpC-producing E. coli prior to plating on selective agar, which is a technique used in some prevalence studies ( Hordijk et al, 2013 ; Gonggrijp et al, 2016 ; Hutchinson et al, 2017 ). In addition, selecting one isolate per sample may not be sufficient to reflect the bacterial heterogeneity associated with an ecological niche ( Venturini et al, 2022 ), therefore, analysing multiple isolates per sample is beneficial in prevalence studies. The age of the study population is also a crucial factor to consider.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this study did not use a pre-enrichment step for ESBL- and AmpC-producing E. coli prior to plating on selective agar, which is a technique used in some prevalence studies ( Hordijk et al, 2013 ; Gonggrijp et al, 2016 ; Hutchinson et al, 2017 ). In addition, selecting one isolate per sample may not be sufficient to reflect the bacterial heterogeneity associated with an ecological niche ( Venturini et al, 2022 ), therefore, analysing multiple isolates per sample is beneficial in prevalence studies. The age of the study population is also a crucial factor to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Another severe disease reported in horses is pneumonia caused by MDR isolates of Klebsiella pneumoniae, a putative zoonotic pathogen [36]. It was recently demonstrated that multiple clones of K. pneumoniae carrying different antibiotic resistance genes can be copresent in a single episode of infection, with each clone being sensitive to the lytic activity of different bacteriophages [37]. This study, which emphasizes the use of bacteriophage typing as part of routine testing, is a basis for the identification and characterization of new phages with lytic activity that might be considered for future application against MDR K. pneumoniae.…”
Section: Horsesmentioning
confidence: 99%
“…Inhibiting these genes or proteins could potentially restore sensitivity to antibiotics in multidrug-resistant strains. 59 Recently, Venturini et al 60 focused on these genes and suggested clinicians can use them as diagnostic markers to identify multidrug-resistant strains of KP and PA, enabling informed decisions on selecting appropriate antibiotic treatments for better patient outcomes. In personalized treatment strategies, some of the MDR genes also contribute to allowing tailored treatment based on the Gene Expr genetic characteristics of the infecting strain, thereby optimizing patient outcomes.…”
Section: Go and Pathway Enrichment Analysismentioning
confidence: 99%